FORMULATION AND EVALUATION OF CEFUROXIME AXETIL GRANULES FOR ORAL SUSPENSION - Aditya Jaitly; Sharma, Rahul; Zafar, Rizwan (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The aim of this study is formulation and evaluation of cefuroxime axetil (CA) granules for oral suspension and to compare its in vitro bioavailability with Innovator Product. Methods: The granules of CA were prepared by wet granulation method. Six formulations of varying composition of ingredients were prepared. Preformulation studies were performed. The suspension was evaluated for its flow property, in vitro dissolution study, and assay. Results: Preformulation parameters show that the flow property of powder is poor. The suspension was successfully prepared by wet granulation method. The flow property of granules varied form fair to excellent in different formulations. The f2value ranges from 25 to 77. Conclusion: With a better release characteristic and excellent flow property, the formulation F6 is considered as the final formulation with an f2 value of 77 and assay of 99.7%.